Correlation between Arterial Feeding Embolization and Pleural Effusion Dynamics in Breast Cancer Patients - Iskandar, Edward; Tangkilisan, Adrian; Sukanto, Wega (e-CliniC, 2025)
Abstract: Breast cancer is the most common malignancy in women and a leading cause of malignant pleural effusion (MPE). Arterial feeding embolization, as performed in transarterial chemo-embolization (TACE), has the potential to reduce effusion production by obstructing tumor blood supply. This study aimed to evaluate the correlation between arterial embolization and pleural effusion dynamics in patients with breast cancer. This was a prospective cohort study conducted at Prof. Dr. R. D. Kandou Hospital, Manado, from 2022 to 2024. Patients diagnosed with breast cancer were randomly assigned to the TACE or control group. Superselective embolization was performed using a microcatheter and a selected embolic agent to occlude the blood supply to the target lesion. Data were analyzed using SPSS v26 with Shapiro-Wilk normality test, t-test or Mann-Whitney U test, and linear regression. Study phases included subject selection, randomization, and data analysis. The results showed that a total of 21 female patients with breast cancer (mean age 52.19±9.17 years) were enrolled. Eleven patients (52.4%) underwent TACE, while ten (47.6%) did not. Pleural effusion was observed in four patients (19%), more frequently in the non-TACE group (30%) compared to the TACE group (9.1%), though the difference was not statistically significant (p=0.439). Multivariate analysis also revealed no significant association between arterial embolization and pleural effusion (p=0.244; R²=0.071), indicating a low predictive value. Arterial feeding embolization via TACE demonstrated clinical potential in reducing pleural effusion among breast cancer patients, although the results were not statistically significant. The limited efficacy may be attributed to the complex tumor vascularization and heterogeneous biological responses. A multimodal therapeutic approach remains necessary for optimal MPE management. In conclusion, although arterial embolization may clinically reduce tumor perfusion and subsequent effusion formation, this study found no significant correlation between the procedure and pleural effusion reduction. Therefore, arterial embolization alone may not be sufficient as a standalone treatment strategy for managing MPE in breast cancer patients. Keywords: breast cancer; malignant pleural effusion; transarterial chemoembolization